Comparision of antimicrobial alternatives in diets for nursery pigs - Keegan, T.P.; Hasted, C.W.; DeRouchey, Joel M.; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 720 weanling pigs (12.8 lb and 18 ± 2 d of age, PIC) was used in two trials to determine the effectiveness of antimicrobial alternatives in diets for nursery pigs. Pigs were fed one of 8 experimental diets: 1) Control with no antibiotics or antimicrobial alternatives, 2) carbadox (50 g/ton), 3) Probios® (1.6% from d 0 to 14 and 0.8% from d 14 to 21), 4) BioSaf® (0.3%), 5) Biomate Yeast Plus® (0.1%), 6) Bio-Mos™(0.3%), 7) Bio-Plus® 2B (0.05%), or 8) LactoSacc® (0.2%). BioSaf®, Biomate® Yeast Plus®, and Lacto Sacc® are all concentrated forms of selected live yeast cells, while Bio-Mos™ is a mannanoligosaccharide derived from yeast. Probios® is a form of lactic acid bacteria and Bio Plus® 2B contains two bacillus strains. Overall (d 0 to 27), pigs fed the diet containing carbadox had greater (P<0.05) ADG compared to pigs fed all other diets. Pigs fed the diet containing carbadox also had greater (P<0.05) ADFI compared to pigs fed BioSaf, Yeast Plus, Bio Mos, Bio Plus 2B and Lacto Sacc. Pigs fed the diet containing Bio Plus 2B had lower (P<0.05) ADFI compared to pigs fed the diet containing Probios. Pigs fed the diet containing Probios had the poorest (P<0.05) F/G compared pigs fed all other diets except the control diet. In addition, pigs fed the diet containing carbadox had improved (P<0.05) F/G compared to pigs fed the control diet or the diet containing Probios. In conclusion, the addition of carbadox – but not antimicrobial alternatives – in nursery pig diets resulted in a consistent improvement in growth performance over pigs fed the control diet. Although pigs fed antibiotic alternatives showed no improvement over carbadox, a numeric improvement in F/G for some products over pigs fed the control diet warrants further investigation.
Keywords: Nursery pig; Carbadox; Feed additive; Swine